Clinical Differentiation Between Lumbar Spine and Hip Examination Findings in an Individual With Low Back and Leg Pain: A Case Report. - Clark, Erin; Schneider, Rebecca; Davenport, Todd E. (Orthopedic Physical Therapy Practice, 2025)
Background: The cross-innervation of structures and overlap of symptom presentation in the lumbopelvic and hip regions can make it difficult for clinicians to effectively identify and treat the primary pain-generating structure. The purpose of this case report is to highlight the importance of a thorough evaluation and screening of the hip and lumbar spine in patients presenting with low back pain (LBP). Case Presentation: The patient was a 64-year-old male referred to physical therapy by his primary physician for evaluation and treatment of LBP. The patient received manual therapy, exercise, and education directed at identified impairments. Outcome: The patient was discharged after 6 visits over 12 weeks. The patient's Focus on therapeutic Outcomes score improved from 70 to 83 out of 100. Discussion: This case report emphasizes the importance of early identification of contributing pain regions and the development of an individualized treatment plan for patients with presentations of low back with leg pain.